THE STYLES' VARIATION CONTAINED IN FRENCH MEDIA - Tobing, Roswita Lumban; Rahayu, Siti Perdi; Rohali, Rohali; Utami, Nastiti (LITERA, 2020)
The use of language styles has a widely varied purpose to convey information that is not explicitly expressed by the speaker. This study is aimed at describing the form and function of the styles contained in the French media. The subjects of this research are phrases and sentences contained in the CDP Lyrics in the Blonde albums, alcoholic beverages and advertisement aplle in French-language magazines, and in the speech by Franí§ois Hollande in "˜Le Figaro' newspaper. Data collection is done by observation and recording techniques using data tables. Data analysis uses the agih method. The analysis of the language style functions is done by using the speech components of SPEAKING. The validity is obtained through semantic validity and reliability through intra-rater reliability. The results of the study show that the style of language in the media is necessary for speech so that the content of communication is more beautiful and attractive. Language style functions depend on the context and purpose of the speech. The most dominant function in the lyrics of the song is the poetic, which prioritizes beauty. In Alcoholic Beverage Ads, the expressive function becomes dominant to make the advertisement more alive. In the Apple Product Advertising on the Internet, the language function is referential for emphasizing the topics described. Keywords: language style, form and function VARIASI GAYA BAHASA DALAM MEDIA PERANCIS Abstrak Penggunaan gaya bahasa mempunyai tujuan yang sangat bervariasi untuk menyampaikan informasi yang tidak akan dinyatakan secara eksplisit oleh si penutur. Penelitian ini bertujuan untuk menjelaskan bentuk dan fungsi gaya bahasa pada media komunikasi yang berupa lagu, iklan, dan Surat Kabar berbahasa Prancis. Subjek penelitian ini adalah frasa dan kalimat yang terdapat dalam Lagu CDP pada album Blonde, iklan minuman beralkohol, iklan aplle dalam majalah berbahasa Prancis, dan Pidato Franí§ois Hollande dalam Surat Kabar Le Figaro. Pengumpulan data dengan metode simak dan teknik catat dengan tabel data. Analisis data menggunakan metode agih. Penentuan fungsi gaya bahasa menggunakan metode padan referensial. Fungsi penggunaan gaya bahasa dianalisis dengan komponen tutur SPEAKING. Keabsahan data melalui validitas semantis, reliabilitas dengan intra-rater. Hasil penelitian menunjukkan bahasa gaya bahasa yang paling menonjol pada lagu adalah asonansi dan hiperbola, pada iklan minuman beralkohol adalah aliterasi dan hiperbola, pada pidato Franí§ois Hollande adalah repetisi dan hiperbola, pada iklan apple adalah asonansi dan aliterasi. Fungsi bahasa yang sering muncul adalah referensial kecuali pada iklan minuman beralkohol, yang dominan adalah fungsi emotif. Fungsi gaya bahasa tergantung pada konteks dan tujuan. Gaya bahasa di media diperlukan agar konten indah dan menarik. Kata kunci : Gaya Bahasa, Bahasa Prancis, Bentuk dan Fungsi